Acoustic reflectors are visible in the right heart during radiofrequency ablation of varicose veins. (September 2015) - Sounderajah, V; Moore, HM; Thapar, A; Lane, TRA; Fox, K; Franklin, IJ; Davies, AH
Objective: Cerebrovascular events have been noted after foam sclerotherapy for varicose veins. One hypothesis is migration of microemboli to the brain through a cardiac septal defect. The aim of this study was to identify whether acoustic reflectors are found in the right side of the heart during radiofrequency ablation of varicose veins, as neurological events are not reported during these procedures. Methods: Transthoracic echocardiography was performed during local anaesthetic radiofrequency ablation (VNUS ClosureFast) of the great saphenous vein in 14 patients. An apical view was captured at the start of the procedure, during each cycle of heating and at 1 min post-treatment. Patients were monitored for 1 h. Video loops were read by an independent cardiologist. The presence of acoustic reflectors was classified as: 0 = absent, 1 = occasional, 2 = stream, 3 = complete opacification. Results: Loops were of diagnostic quality in 11/14 (79%) patients. After the second cycle of heating, acoustic reflectors moving through the right heart were seen in 5/11 (45%) patients. These were classified as grade 1 in four patients and grade 2 in one patient. No acoustic reflectors were seen in the left heart. No neurological symptoms were reported. Conclusion: Acoustic reflectors in the right heart are a common finding during radiofrequency ablation of varicose veins. Considering the prevalence of cardiac septal defects (17%), more neurological events would be expected if these particles were indeed responsible for these events. Further work is required to elicit the mechanisms underlying neurological complications following sclerotherapy.